THE CORRELATION LANGUAGE AND GENDER AS WOMAN’S LANGUAGE IN THE MAIN CHARACTER IN THE CONFESSION OF A SHOPAHOLIC’S MOVIE - Rahma Putri Ramadhani; Siti Hafsah; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2019)
This research studies about the correlation language and gender with the variety of woman’s language feature in the main character Rebecca Bloomwood in the Confession of Shopaholic movie. There are two objectives that become the purpose of this study; 1) To find the variety of woman’s language feature in the main character Rebecca Bloomwood in the Confession of Shopaholic movie and 2) To find the woman’s language correlate to gender in the main character in the Confession of Shopaholic movie. The theory used in this research is the Sociolinguistic approach by using the theory of Robin Lakoff about woman’s language features and women’s language correlate to gender. The methodology used in this study is qualitative research to explain the data, because the data are analyzed and described in the form of words and sentences. The data are taken from the conversations uttered by the main character as female character. The result of the research, the researcher finds ten variety of woman’s language such as precise color terms, avoiding using strong word, empty adjective, tag question, avoiding using strong word, lexical hedges, intensifier, emphatic stress, hypercorrect grammar, and super polite form. Regarding the reason by using the feature is most the feature of variety woman’s language has been found in the main character. Those features show woman’s correlations to gender that women tend to reflect uncertainty, and their lack of confidence in conversation. This research finds woman’s language is super polite than man, women’s talk more evaluative and emotional than man’s language.